ANALYSIS OF THE IMPACT OF WORKLOAD AND WORK STRESS ON JOB SATISFACTION WITH MOTIVATION AS INTERVENING VARIABLE - Kirana, Kusuma Chandra; Lukitaningsih, Ambar; Londin, Dorce Marchiliya (Universitas Brawijaya, Indonesia, 2021)
This study aims to analyze the impact of workload and work stress on job satisfaction with the motivation of a solution to the intervention of the nurse team covid-19 Maluku Southeast. Data collection was carried out through the distribution of questionnaires to 33 nurses. As for the method used in this study, there are modeling research methods using partial analysis tools at least square. The findings of this study are: The workload is not proven to have a negative and significant effect on motivation, work stress is not proven to have a negative but significant impact on motivation, the workload is not proven to have a negative and significant impact on job satisfaction, the work stress is proven to have a negative but insignificant effect on job satisfaction, the motivation proven to have a positive and significant impact on job satisfaction, Workloads have not proved to affect work satisfaction through motivation, work stress has proved to affect work satisfaction through motivation. The author suggests that research on job satisfaction can use variables other than workload, job stress, and motivation to reveal other contributions outside of these variables.